The effectiveness of corporate governance hybrid models in emerging markets : the case of the Issuer Recognition program (2021)
Research question/issue What is the Issuer Recognition (IR) program, and what has been its impact as a new and replicable corporate governance hybrid form used in the Colombian Securities Exchange (CSE)? Research findings/insights We find that the IR program has significantly increased the information disclosure level of the adopting firms. This set of firms that were among the opaquest businesses in the region in 2010 ranked at the top in terms of disclosure in 2017. In addition, using as a benchmark the rate of implementation of the Colombian Country Code (soft law), we are able to show that the IR program serves as a strong signaling mechanism in the Colombian capital market. Theoretical/academic implications The literature is not conclusive on the effectiveness of hard law and soft law regulations in the emerging markets. In this paper, we show that hybrid models, such as the innovative Colombian's IR, might serve as a solution for the effective implementation of good corporate governance practices at the country level. Practitioner/policy implications The advantages and impacts of hybrid models are relatively unknown for policymakers, stock exchange promoters, and agency surveillance bodies, given the lack of empirical evidence of their application's effects. This paper seeks to increase the awareness of these models and call for their development and implementation, especially in emerging markets.